2021
DOI: 10.5194/angeo-39-945-2021
|View full text |Cite
|
Sign up to set email alerts
|

Space weather study through analysis of solar radio bursts detected by a single-station CALLISTO spectrometer

Abstract: Abstract. This article summarises the results of an analysis of solar radio bursts (SRBs) detected by the Compound Astronomical Low-cost Low-frequency Instrument for Spectroscopy and Transportable Observatory (CALLISTO) spectrometer hosted by the University of Rwanda. The data analysed were detected during the first year (2014–2015) of the instrument operation. Using quick plots provided by the e-CALLISTO website, a total of 201 intense and well-separated solar radio bursts detected by the CALLISTO station loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The results from current study also indicate that analyzed SRBs were associate by ionospheric disturbances as demonstrated by TEC enhancement. The findings of this study demonstrate that it is possible to track well the progress of solar cycle 25 and forecast the intensity of associated space weather phenomena by analyzing and characterizing the physical features accompanying Type II SRBs observed from the ground (Ndacyayisenga et al, 2021a).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The results from current study also indicate that analyzed SRBs were associate by ionospheric disturbances as demonstrated by TEC enhancement. The findings of this study demonstrate that it is possible to track well the progress of solar cycle 25 and forecast the intensity of associated space weather phenomena by analyzing and characterizing the physical features accompanying Type II SRBs observed from the ground (Ndacyayisenga et al, 2021a).…”
mentioning
confidence: 79%
“…Only 7 of the 31 type II radio bursts studied, on the other hand, are not a potential event to disrupt space weather because they are not associated with a CME or have an immediate space weather impact, whereas the rest can be used to track geomagnetic storms within the next five days from the onset of associated CMEs. Solar radio bursts are among the earliest observed signatures of erupting events in the solar corona (Salmane et al, 2018;Ndacyayisenga et al, 2021a).…”
Section: March 24 -April 3 2022mentioning
confidence: 99%